Behavior of 3D-printed polymers under monotonic torsion - A database of 15 different materials - Sadaghian, Hamed; Khalilzadehtabrizi, Sahand; Farzam, Masood; Dehghan, Somaiyeh (ELSEVIER, 2022)
A comprehensive study was carried out to assess the performance of various 3D-printed polymers under monotonic torsion. To the best knowledge of the authors, studies on the torsional behavior of 3D-printed polymers are limited. Fifteen different materials were 3D-printed using the fused deposition modeling (FDM) approach in a flat orientation. For each series, two raster angles i.e., +/- 45 degrees and 0 degrees /90 degrees degrees were considered. Circular specimens with a diameter of 10 mm were subjected to a torsional moment with a rate of 0.2 mm/min. Results showed superior performance of specimens with a raster angle of +/- 45 degrees in comparison to their 0 degrees/ 90 degrees counterparts. Besides, shear moduli and linear energy absorption per unit volume of the specimens were compared and discussed. Specimen PAHT-CF (polyamide high temperature; CF: carbon fiber) (average shear stress: 49.3 MPa) had the overall best performance in all the investigated parameters; failure of specimens except for polypropylene (PPJET), and thermoplastic polyurethane (TPU) was brittle and sudden and initiated between layers rather than inside layers (i.e., filament fracture); incorporation of carbon fiber didn't necessarily contribute to improved torsional capacity or ductility. Finally, idealized multi-linear curves were proposed which can aid in the numerical simulation of various 3D-printed polymers.
Keywords: 3D-printed polymer; Monotonic torsion; Fused deposition modeling (FDM); Fracture; Raster angle; Engineering; Materials Science